Synthesis and Design of New Gemcitabine Derivatives as In Vitro α-Glucosidase Inhibitors - Ali J. Radhi (Journal of Global Pharma Technology, 2016)
A new series of gemcitabine derivatives containing imine structure have been prepared efficiently by reaction gemcitabine with some aromatic aldehydes. The structures of the imine derivatives were confirmed by many spectroscopic methods such as elemental analysis, FTIR and NMR spectroscopy. The α-glucosidase activity was evaluated of end compounds in vitro. All imine derivatives  were showed α-glucosidase inhibition with IC50 values 223±1.24, 244±2.32, 94±1.01, 268±1.35, 387±2.12, 78±1.42, 145±1.32, 54±2.41 µM respectively, when compared with the control drug (IC50 = 784.35 ± 2.41 µM).Compound (g8) have higher therapeutic indices, representing possible promising roles. Overall result suggests that gemcitabine derivatives containing Schiff base structure (g1-g8) could be lead a new design in this study of novel α-glucosidase inhibitor.Keywords: Gemcitabine, Imine, Diabetes mellitus and α-Glucosidase Inhibitors.